LINGUISTIC MEANS OF FORMULATING RESOLUTION IN DEBATE - Maratova, A.M. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
Today, debates are very popular and play an important role in various spheres of public life. When entering a debate, the speaker must convince the audience of the correctness of his speech by supporting rhetorical criticism. There are different topics in the debate, such as sociology, political, religious, and science and fiction. These days, new terms or phrases are appearing. For debaters, it is difficult to find their meaning in fifteen minutes.
Keywords: debate; resolution; rhetoric; motion; speaker